Dinamika Psikologis Individu dalam Merawat Lansia yang Mengalami Demensia - Djapar, Robert Philip; Hanif Firdaus Gitya Iman; Hendriani, Wiwin (Buletin Riset Psikologi dan Kesehatan Mental, 2025)
The purpose of this study was to examine the psychological dynamics of caregivers of parents with dementia. This qualitative research used phenomenological approach and utilized Interpretative Phenomenological Analysis (IPA) for data analysis. The interviews were conducted with two female respondents, aged 46 and 47 years, who were caring for a parent (mother) with dementia. The results of data analysis found the process of accepting the diagnosis and medical rationalization of caregivers towards the condition of patients with dementia, the existence of identity transformation and caregiver role conflicts in the family, emerging emotional navigation in caregivers to cope with stress and relational burden, psychological fatigue both cognitively and emotionally, the use of nurses and acceptance of social support as a form of adaptive coping.